Laodbudgeting sebagai Alternatif Mengelola Keuangan Generasi Z - fitriani, ninis (Maliki Interdisciplinary Journal, 2025)
Generation Z, comprising individuals born between the mid-1990s and early 2010s, faces complex financial challenges amid the ever-changing dynamics of the global economy. With rising education costs, concerning student debt, and escalating living expenses, it is crucial for this generation to find effective financial management methods. Laodbudgeting emerges as an innovative solution that combines traditional budgeting principles with advanced digital technology. This method not only allows users to track expenses and manage budgets in real-time but also encourages a better understanding of financial literacy. By utilizing apps and digital tools, Generation Z can develop discipline in spending, save for the future, and plan finances in a more adaptive manner. This article aims to explore the potential of laodbudgeting as a relevant and practical approach to financial management for Generation Z, as well as to identify the benefits and challenges that may arise in its implementation.